Integrasi Nilai-nilai Kewarganegaraan dan Sosial dalam Pembelajaran Ekonomi untuk Membentuk Karakter Siswa yang Berintegritas - Hafizah, Hafizah; Imamuddin, M.; Widianita, Rika; Ridhah, Habibatur; Anisah, Ariyun (FKIP Universitas Islam Jember, 2025)
This study aims to describe and analyze the integration of civic and social values in Economics learning at senior high schools in Bukittinggi, West Sumatra. A qualitative descriptive approach was employed, involving interviews, classroom observations, and document analysis with teachers, students, and principals from three selected high schools. The total number of participants in this study was 73 individuals selected purposively based on the research objectives and data requirements. The results show that value integration occurs through three main stages: lesson planning, classroom implementation, and assessment. The dominant values integrated include honesty, responsibility, cooperation, social justice, and environmental awareness. Contextual and project-based learning approaches were found effective in instilling these values. The impact is evident in students’ improved integrity, discipline, empathy, and ethical decision-making in economic contexts. Although teachers face challenges such as limited time and lack of integrative guidelines between subjects, these are addressed through interdisciplinary collaboration and teacher working groups (MGMP). Overall, the integration of civic and social values in Economics learning significantly contributes to shaping students’ ethical character and responsibility as citizens.